If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) = 5 Reorder the terms: 3(-3 + x) = 5 (-3 * 3 + x * 3) = 5 (-9 + 3x) = 5 Solving -9 + 3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3x = 5 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 5 + 9 3x = 5 + 9 Combine like terms: 5 + 9 = 14 3x = 14 Divide each side by '3'. x = 4.666666667 Simplifying x = 4.666666667
| C(x)=x^2-14x+49 | | 25x^2-17x=0 | | -14+3(x+10)=-8-3(p+12) | | 3x^2-3x-1=0 | | x^2-14x-8051=0 | | 2(k+4)-3k=14 | | 6(1+3m)=-8-2(p+12) | | x^2-21x-1=0 | | 5x+8=7x | | .5m=3.5 | | 3c^2-10c+8=0 | | y=x^2+2x+26 | | 2x^2-3x-54=0 | | 15-.75g=13-.50g | | 16=3x-2 | | -5=11+4j | | 12=60-6r | | 24x-(6+5x)=51 | | 4x-3-3x=12+2x | | 2+2p=-17 | | (x+15+10)*12=372 | | 33y-3=8 | | -56=7d | | 34h+6g+34r-46g+4h-45r=1453 | | 4n-3=105 | | 3(2t-1)+2t=6-t | | 13x=15x+14 | | -12m=-72 | | 4n^2-20n+25=0 | | Y=4x^2-12x+9 | | (10+15+x)*12=372 | | x^2+66=0 |